Patient-reported symptoms following diagnosis in esophagus cancer patients treated with palliative intent. Issue 8 (20th January 2020) - Davis, Laura E; Gupta, Vaibhav; Allen-Ayodabo, Catherine; Zhao, Haoyu; Hallet, Julie; Mahar, Alyson L; Ringash, Jolie; Doherty, Mark; Kidane, Biniam; Darling, Gail; Coburn, Natalie G
Summary: The majority of patients with esophagus cancer have advanced-stage disease without curative options. For these patients, treatment is focused on improving symptoms and quality of life. Despite this, little work has been done to quantify symptom burden for incurable patients. We describe symptoms using the Edmonton Symptom Assessment System (ESAS) among esophagus cancer patients treated for incurable disease. This retrospective cohort study linked administrative datasets to prospectively collected ESAS data of non-curatively treated adult esophagus cancer patients diagnosed between January 1, 2009 and September 30, 2016. ESAS measures nine common cancer-related symptoms: anxiety, depression, drowsiness, lack of appetite, nausea, pain, shortness of breath, tiredness, and impaired well-being. Frequency of severe symptoms (score ≥ 7/10) was described by month for the 6 months from diagnosis for all patients and by treatment type (chemotherapy alone, radiotherapy alone, both chemotherapy and radiotherapy, and best supportive care). A sensitivity analysis limited to patients who survived at least 6 months was performed to assess robustness of the results to proximity to death and resulting variation in follow-up time. Among 2, 989 esophagus cancer patients diagnosed during the study period and meeting inclusion criteria, 2, 103 reported at least one ESAS assessment in the 6 months following diagnosis and comprised the final cohort. Patients reported a median of three (IQR 2–7) ESAS assessments in the study period. Median survival was 7.6 (IQR 4.1–13.7) months. Severe lack of appetite (53.1%), tiredness (51.1%), and impaired well-being (42.7%) were the most commonly reported symptoms. Severe symptoms persisted throughout the 6 months after the diagnosis. Subgroup analysis by treatment showed no worsening of symptoms over time in those treated by either chemotherapy alone, or both chemotherapy and radiation. Results followed a similar pattern on sensitivity analysis. Patients diagnosed with incurable esophagus cancer experience considerable symptom burden in the first 6 months after diagnosis and the frequency of severe symptoms remains high throughout this period. Patients with this disease require early palliative care and psychosocial support upon diagnosis and support throughout the course of their cancer journey.